2010
DOI: 10.1083/jcb.200907116
|View full text |Cite
|
Sign up to set email alerts
|

Notch ligand activity is modulated by glycosphingolipid membrane composition in Drosophila melanogaster

Abstract: Endocytosis of the transmembrane ligands Delta (Dl) and Serrate (Ser) is required for the proper activation of Notch receptors. The E3 ubiquitin ligases Mindbomb1 (Mib1) and Neuralized (Neur) regulate the ubiquitination of Dl and Ser and thereby promote both ligand endocytosis and Notch receptor activation. In this study, we identify the α1,4-N-acetylgalactosaminyltransferase-1 (α4GT1) gene as a gain of function suppressor of Mib1 inhibition. Expression of α4GT1 suppressed the signaling and endocytosis defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…A broad range of SBDs have been identified in phylogenetically-distant proteins including microbial [9], [10], insect [7] and human proteins [11], [13], [14]. These discoveries have enabled to draw a photofit of the SBD, which is typically a looped domain with a central aromatic residue and a basic amino acid at each end [1].…”
Section: Discussionmentioning
confidence: 99%
“…A broad range of SBDs have been identified in phylogenetically-distant proteins including microbial [9], [10], insect [7] and human proteins [11], [13], [14]. These discoveries have enabled to draw a photofit of the SBD, which is typically a looped domain with a central aromatic residue and a basic amino acid at each end [1].…”
Section: Discussionmentioning
confidence: 99%
“…One is that the phenotype is caused by lack of elongated GSLs, as these play important roles in cell recognition and signaling by confining signal transduction proteins to selected membrane compartments (4). In addition, elongated GSLs directly interact with membrane proteins that modulate receptor activation via modification of receptor dimerization, recycling, and galectin-mediated clustering (26)(27)(28)(29). Importantly, GlcCer and MacCer are minor components of the GSL repertoire in extracts from Drosophila embryos and larvae because they represent biosynthetic intermediates for elongated GSLs (30).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these data indicated that the N-terminal parts of α-synuclein and Aβ share a common motif with high structural homology and significant sequence similarity. Since both the 34-45 fragment of α-synuclein [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], the human cellular prion protein PrP (192-209), a 14-mer GM1-binding peptide selected from a phage display library, and Aβ (fragment [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Identical amino acids are indicated in yellow ( ⁎ ) and amino acids of the same class (conserved substitutions such as basic for basic or aromatic for aromatic) in blue (:).…”
Section: A Common Gbm In Amyloidogenic Proteinsmentioning
confidence: 99%
“…21 This domain, initially identified in the V3 loop of the HIV-1 surface envelope glycoprotein gp120, 22 has been found later in PrP and Aβ, 10,23 bacterial toxins and adhesins, 24 membrane proteins and receptors, 25,26 and more recently in α-synuclein. 14 So far, the strategy to detect a SBD has been (i) to perform structure similarity searches with the combinatorial extension (CE) method, 10,27 using the prototype HIV-1 gp120 V3 loop as template, or (ii) to look for the presence of short motifs containing the key amino acid residues listed above (aromatic, Gly and/or Pro, basic), especially when the three-dimensional structure of the protein is unknown.…”
Section: Introductionmentioning
confidence: 98%